2007
DOI: 10.1159/000099226
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of Vocal Cord Paralysis

Abstract: Objective: Vocal cord paralysis (VCP) is a sign of a certain underlying disease, a diagnosis which can be attributed to various causes. This study intends to analyze the contemporary etiology of VCP in a tertiary medical center. Materials and Methods: A retrospective review of medical records from June 2000 to December 2004 of hospitalized patients with VCP was done to determine the etiology. Results: Two hundred and ninety-one patients with a determined etiology were identified, consisting of 176 males and 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
71
2
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 33 publications
10
71
2
4
Order By: Relevance
“…Consequently, the opening became asymmetrical, which led to some minor differences in velocities for the same areas of the opening. Again, for areas below about 40 mm 2 , there is a visible increase in the maximum velocity, albeit less pronounced than in the case of ΔP. For areas between 20 and 40 mm 2 , wmax increased from 2.5 to 5 m/s.…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations
“…Consequently, the opening became asymmetrical, which led to some minor differences in velocities for the same areas of the opening. Again, for areas below about 40 mm 2 , there is a visible increase in the maximum velocity, albeit less pronounced than in the case of ΔP. For areas between 20 and 40 mm 2 , wmax increased from 2.5 to 5 m/s.…”
Section: Resultsmentioning
confidence: 69%
“…It was determined that resistance to airflow, expressed as the pressure drop ΔP, depends on the area of the glottic opening and is virtually independent of its shape. During free breathing, a steep rise in ΔP occurs for areas below about 40 mm 2 . It can be concluded that below this area even a minor enlargement of the glottis may significantly improve quality of breathing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there are four major causes: surgery, malignancy, idiopathic and neck trauma. Previous studies, such as those performed by Chen and Ko, have demonstrated that thyroidectomy is the most common surgical cause of vocal cord paralysis, followed by cardiac surgery [7,8]. There have only been two reported cases of vocal cord paralysis following oesophageal stenting or dilatation procedures.…”
Section: Discussionmentioning
confidence: 99%